Tah-Keh eller Dö-Gö? - Hamström,Tobias (2025)
This work aims to present differences in various ways of learning double-tonguing on the bassoon, to try the presented methods, and to discuss and reflect in order to determine which of the presented methods is the best regarding evenness, flexibility, and suitability in a musical context. All of the methods have some common similarities but also defining differences. The conclusion is that the Mannheimer- and Formáček/Tvrdý-methods are the most successful in their respective aspects, except regarding evenness and equality between starting of notes; where the best result is instead achieved by combining elements from all the presented methods.
Keywords: fagott; dubbeltunga